"Ungdomsrån" - uppkomsten av ett begrepp (Sociologisk Forskning, 2006)
This article presents results from a research project, the main aim of which is to analyze media representations of youth robberies in a number of Swedish newspapers during the five year period 1998-2002. Prominent patterns in the way media report these crimes are mapped using content analysis, and discussed in terms of their potential consequences. The theory of so called moral panics plays an important part in these discussions. When it comes to the growing ‘racialization of youth crime in public debate, the youth robberies are a phenomenon - as well as a concept - vested with great symbolic powers. It is thus important to scrutinize the ways in which interpretations, values and attitudes are formed in this area.